Experimental study of scour around circular and elongated bridge piers with and without pier slot - Azevedo, M. L. (2014)
This work describes an experimental study of clear water scour around bridge piers, placed in a cohesionless bed of sediments. The use of pier slot as a flow-altering countermeasure against bridge scour is evaluated, in the case of circular and elongated piers. Four piers with 20 mm of transversal dimension were used, with one circular pier and one elongated pier that featured a slot, corresponding to a flow-altering countermeasure. Sand with a mean diameter of 0.33 mm was used, in a free surface flow with a water depth equal to 5 cm and a flow rate equal to 12.96 m3h-1. The temporal evolution of the maximum scour depth was studied and the topography of the scour cavity was analysed. The scour hole maximum depth was higher in case of the simple piers, when compared with piers with slot. It was observed that the scour hole maximum depth was smaller in case of elongated piers, when compared with circular piers. The bed slope upstream from the pier was higher than the one observed downstream from the pier. In case of pier slot measurements, both upstream and downstream slopes were reduced, when compared with the simple pier measurements. When comparing the initial and the equilibrium phases of scour, it was observed that bed slopes decrease as the duration of the experiments increases.